First report of bovine coenurosis in North Macedonia - Aleksandar Cvetkovikj; Ljubica Rashikj; Boris Dimitrievski; Aleksandar Trajchovski; Ivana Shikoska; Petre Dimov; Iskra Cvetkovikj; Jovana Stefanovska (Macedonian Veterinary Review, 2024)
Coenurosis is a cystic parasitic disease affecting ruminants and other mammals worldwide. The disease is caused by Coenurus cerebralis, the larval stage of the tapeworm Taenia multiceps. Sheep and goats are frequently infected, while cases in cattle are rare. Here we describe the first recorded case of bovine coenurosis in North Macedonia. The diagnosis was based on the neurological clinical signs and the postmortem findings of a 1-year-old bull with symptoms typical for coenurosis, i.e. ataxia, circling movements, mild depression and impaired vision. Postmortem, a cyst was found in the left cerebral hemisphere and was confirmed as fertile Coenurus cerebralis by parasitological analysis. These findings suggest that coenurosis should be considered part of the differential diagnosis in cattle with neurological symptoms. This highlights the need for routine surveillance of this disease in livestock and proactive tracking of the parasite in the final hosts to enhance disease management.